Modelling structures of computer networks - Пасічник, Володимир Володимирович; Іванущак, Наталія Михайлівна (Eastern-European Journal of Enterprise Technologies, 2013)
The object of research is computer systems, the processes of evolutionary dynamics of which are described on the basis of the concepts of statistical physics of complex networks. Computer networks are not static, therefore, in order to understand the dynamics of their development, it is necessary to discover the principles of their evolution. The present study presents the model and the formulated rules for the structuring of complex computer networks with the application of the graph theory apparatus. The algorithm of modeling and the adequacy of description by means of the real structure model have been illustrated by the generation of stochastic graph with the application of statistical characteristics of real computer networks, such as “BV-Star & FoxNet”, “The City Cable Television” and “DSS-Group” in Chernivtsi. The empirical data as well as the original method of network generation for the assigned law of degree distribution of nodes enabled us to carry out network modeling in the environment «Processing» and perform the comparative analysis and systematization of the main characteristics. Performed estimations, the utilized modeling algorithms, and the validity of applying mathematical tools enable us to make a conclusion about the accuracy and adequacy of the application of the suggested model to real structures. The proposed algorithms of modeling can be applied in solving the problem of the stability of scale-free computer networks against directed hacker attacks and the distribution of computer viruses